A preparation method of porous silk fibroin freeze-dried preparation

By using pore-forming agent placeholding and secondary lyophilization methods in the silk fibroin complex high molecular weight sodium hyaluronate lyophilized preparation, the problem of excessive redissolution time of the preparation is solved, and the redissolution time is significantly shortened, which is suitable for practical applications.

CN119746159APending Publication Date: 2025-04-04FAVORSUN MEDICAL TECH (SUZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411993971.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing silk fibroin complex high molecular weight sodium hyaluronate lyophilized preparation has a long redissolution time, reaching the hour level, making it difficult to meet the needs of practical applications.

Method used

The pore-forming agent is used to occupy the pore-forming agent, lyophilization, replacement of the pore-forming agent after lyophilization, and perform secondary lyophilization. By increasing the specific surface area of ​​the lyophilized preparation, the redissolution time is shortened.

Benefits of technology

By optimizing the lyophilization process, the redissolution time of silk fibroin complex high molecular weight sodium hyaluronate lyophilized preparation is significantly shortened, from the hour level to the minute level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746159A_ABST
    Figure CN119746159A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of freeze-dried preparations, and a method for preparing a porous silk fibroin freeze-dried preparation, which involves the following process route: preparing a silk fibroin solution, a non-specific stabilizer and a pore-forming agent into a freeze-dried composition liquid, and freeze-drying the preparation using a vacuum freeze dryer after packaging and molding or pre-cooling molding. The freeze-dried preparation is then fully contacted with ethanol to complete the replacement of the pore-forming agent. A secondary vacuum freeze-drying is then performed. Among them, the pre-cooling molding method includes but is not limited to natural low temperature conditions (such as liquid nitrogen, liquid oxygen, etc.) and artificial low temperature environments (such as freeze dryer chambers, ultra-low temperature refrigerators, etc.). Non-specific stabilizers and pore-forming agents can ensure the convenience of the silk fibroin composite freeze-dried preparation in storage, transportation and use, and have a longer shelf life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of freeze-dried preparations, and in particular to a method for preparing a porous silk fibroin freeze-dried preparation. Background Art

[0002] At present, water-light injections are widely used in the medical beauty industry, among which sodium hyaluronate is one of the most important materials for water-light products currently on the market. Sodium hyaluronate water-light preparations are limited by solubility and injectability, and low molecular weight sodium hyaluronate is often selected, but the low molecular weight cannot give it long-lasting moisturizing and micro-area filling properties.

[0003] As a natural polymer material, silk fibroin contains a variety of amino acids, which can stimulate cell proliferation after degradation. Due to the inherent properties of amino acids, silk fibroin is superior to sodium hyaluronate. And as a rigid supporting protein, silk fibroin can provide micro-region filling.

[0004] However, the reconstitution time of the freeze-dried preparation of high molecular weight sodium hyaluronate and silk fibroin is in the order of hours. By adding a pore-forming agent for primary freeze-drying, followed by replacement of the pore-forming agent and secondary freeze-drying, the specific surface area of ​​the freeze-dried preparation is increased, thereby shortening the reconstitution time to the order of minutes. Summary of the invention

[0005] In order to solve the problem of difficulty in re-dissolving the existing lyophilized preparation of silk fibroin combined with high molecular weight sodium hyaluronate, a pore-forming agent occupancy, primary lyophilization, pore-forming agent replacement after lyophilization, and secondary lyophilization were designed, thereby solving the problem of difficulty in re-dissolving the lyophilized preparation of silk fibroin combined with high molecular weight sodium hyaluronate.

[0006] The method for preparing a freeze-dried silk fibroin preparation with controllable molecular weight according to the present invention comprises the following steps: S1 preparing a freeze-dried liquid, which comprises a non-specific stabilizer and a pore-forming agent; S2 molding; S3 freeze-drying; S4 replacing the pore-forming agent; and S5 secondary freeze-drying.

[0007] Further

[0008] S1: preparing a freeze-dried solution, adding sodium hyaluronate, a non-specific stabilizer and a pore-forming agent to a silk fibroin solution and mixing them evenly, wherein the concentration of the silk fibroin includes but is not limited to 1 mg / mL-50 mg / mL.

[0009] S2: Molding, the specific pre-cooling method is one of S21 or S22:

[0010] S21: Packaging and molding, packaging no more than 3.0 g of the freeze-dried component liquid into a mold and precooling;

[0011] S22: Pre-cooling forming, three-dimensional structure with the distance between the farthest two points not exceeding 5mm (for example: cube, cuboid, cylinder, sphere, etc.).

[0012] S3: The pre-cooled preparation is placed in a freeze dryer for primary freeze drying.

[0013] S4: The once lyophilized preparation is immersed in ethanol for pore-forming agent replacement.

[0014] S5: Place the preparation after replacement pore creation into a freeze dryer for secondary freeze drying.

[0015] 1. Further, in step S1, the mass ratio of silk fibroin solution: sodium hyaluronate: non-specific stabilizer: pore-forming agent = 1.0-7.0: 0.5-4.0: 0.5-4.0: 0.5-4.0, the non-specific stabilizer includes one or more of I, II, and III, and the pore-forming agent is shown in IV. Specific examples are as follows:

[0016] Nonspecific Stabilizers:

[0017] I: Sugar substances such as trehalose, lactose, sucrose, maltose, caramel

[0018] II: Sugar alcohols such as mannitol, sorbitol, xylitol, erythritol

[0019] III: Cellulose derivatives such as sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose

[0020] Pore ​​forming agent:

[0021] IV: Polyethylene glycol such as PEG-400, PEG-600, PEG-800, PEG-1000

[0022] A composite freeze-dried preparation of silk fibroin with controllable molecular weight is prepared by the above-mentioned preparation method.

[0023] The interior is loose and porous, with internal pore size ≥10μm, porosity ≥85%, pore size deviation <5μm and re-dissolution time <15min.

[0024] The application of the above-mentioned composite freeze-dried preparation is characterized in that the application includes: dressing products, hydrating products and filling products.

[0025] Specifically, the mechanism and effect of the silk fibroin solution, high molecular weight sodium hyaluronate, non-specific stabilizer and pore-forming agent of the present invention are as follows:

[0026] (1) Effect of silk fibroin solution combined with high molecular weight sodium hyaluronate and non-specific stabilizer:

[0027] The silk fibroin solution is combined with high molecular weight sodium hyaluronate for freeze-drying process. The product disintegrates and the product filling amount cannot be quantified, resulting in the inability to determine the product concentration after reconstitution of the final preparation.

[0028] Diversity of combination effects: When silk fibroin solution is combined with high molecular weight sodium hyaluronate and non-specific stabilizers, the effect may vary depending on the type of stabilizer. For example, some stabilizers may be able to significantly improve the stability of silk fibroin solution, extend its shelf life, and prevent it from denaturing or aggregating when the environment changes. Other stabilizers may only affect certain specific properties of silk fibroin solution, such as viscosity, water retention, etc.

[0029] (2) Effect of silk fibroin solution combined with high molecular weight sodium hyaluronate and pore-forming agent:

[0030] The reconstitution time of the lyophilized preparation of silk fibroin solution combined with high molecular weight sodium hyaluronate is of the order of hours. However, after adding a pore-forming agent for one lyophilization, replacing the pore-forming agent and lyophilizing for a second time, a uniform interconnected structure is formed inside the lyophilized preparation and is connected to the surface of the preparation.

[0031] Preferably, in step S1, the lyophilized composition liquid contains carbohydrate substances including but not limited to trehalose, lactose, sucrose, maltose, caramel and other disaccharides.

[0032] Preferably, in step S1, the sugar alcohol substances in the freeze-dried composition liquid include but are not limited to mannitol, sorbitol, xylitol, erythritol and other sugar alcohol substances.

[0033] Preferably, in step S1, the cellulose derivative material in the freeze-dried composition liquid includes but is not limited to sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and other cellulose derivatives.

[0034] The nonspecific stabilizer includes one or two of the above.

[0035] Preferably, in step S1, in the freeze-dried composition liquid, polyethylene glycol includes but is not limited to PEG-400, PEG-600, PEG-800, PEG-1000 and other molecular weight polyethylene glycols.

[0036] Preferably, in step S1, the concentration of the silk fibroin solution is 1 mg / mL to 50 mg / mL, more preferably 10 mg / mL to 50 mg / mL.

[0037] Furthermore, the mass ratio of silk fibroin solution: sodium hyaluronate: nonspecific stabilizer: pore-forming agent is 1.0-7.0: 0.5-4.0: 0.5-4.0: 0.5-4.0, and more preferably 1.5-6: 0.5-2: 1.2-2: 0.6-0.8

[0038] Preferably, in step S4, the pore-forming method is to immerse the once freeze-dried product in ethanol for pore-forming, and the pore-forming time in ethanol is 5s-20min, more preferably 10s-10min.

[0039] In step S1, the molecular weight (10kDa-80kDa, 80kDa-100kDa, 100kDa-120kDa, 120kDa-160kDa, 160kDa-200kDa, >200kDa) test method of the silk fibroin solution used refers to Appendix B of YY / T 1950-2024 "Silk fibroin for tissue engineering medical devices", and the measured rheological data and viscosity data are imported into FavorsunSmartMolFit "complex intelligent calculation" biopolymer molecular weight calculation commercial software to calculate the number average molecular weight and weight average molecular weight.

[0040] More preferably, in step S1, two kinds of the nonspecific stabilizers are preferably used during use, and the ratio of silk fibroin: nonspecific stabilizer 1: nonspecific stabilizer 2 is 8.5-6.0:0.5-1.0:1.0-3.0.

[0041] A method for preparing a composite freeze-dried preparation of silk fibroin with controllable molecular weight, the applications of which include: water-light products, dressing products and filling products.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] (1) Stability of lyophilized preparations: The use of nonspecific stabilizers increases the stability of lyophilized preparations and avoids the problem of preparation disintegration and inability to quantify use.

[0044] (2) Reduce the re-dissolution time: The re-dissolution time of silk fibroin composite high molecular weight sodium hyaluronate is shortened from hours to minutes due to the optimization of pore structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Example 1: Pore inside the pores of silk fibroin composite high molecular weight sodium hyaluronate and pore-forming agent freeze-dried spheres

[0046] Figure 2 :Comparative Example 1 Silk fibroin composite high molecular weight sodium hyaluronate without adding pore-forming agent freeze-dried ball internal pore picture

[0047] Figure 3 : Example 4, 5 Cell scratch test with silk fibroin macromolecule or micromolecule composite high molecular weight sodium hyaluronate Specific implementation methods

[0049] The technical solution of the present invention is further described below through specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not used to specifically limit the present invention. The drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0050] Sodium hyaluronate is commercially available and has a molecular weight of about 1 million.

[0051] Embodiment 1:

[0052] S1: Preparation of freeze-dried solution: Take 66.67 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g silk fibroin per 100 g solution), 0.5 g sodium hyaluronate, 1 g trehalose, 0.5 g mannitol, and 1 g PEG-400 and gently shake to mix.

[0053] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0054] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -30°C for 30 hours and a vacuum degree of 1 Pa.

[0055] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 2 minutes.

[0056] S5: Place the preparation after replacement pore formation into a freeze dryer for secondary freeze drying. The freeze drying procedure is the same as S3.

[0057] The porous silk fibroin preparation in Example 1 has an internal SEM as shown in FIG. Figure 1 As shown, the interior is loose and porous, the pores inside the freeze-dried preparation are about 10 μm, the porosity is about 85%, and the pore size deviation is <5 μm. The re-dissolution time in water is 15 min.

[0058] Embodiment 2:

[0059] S1: Preparation of freeze-dried solution: Take 77.77 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g silk fibroin per 100 g solution), 1.5 g sodium hyaluronate, 0.5 g sucrose, 1.5 g sodium carboxymethyl cellulose, and 0.6 g PEG-8000, and gently shake to mix.

[0060] S2: Molding: The pre-cooling molding method is to drop the product into liquid nitrogen for molding. The volume of the freeze-dried ball is 35 μL and the particle size is 3.4 mm.

[0061] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -35°C for 28 hours and a vacuum degree of 1 Pa.

[0062] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 5 minutes.

[0063] S5: Place the preparation after replacement pore formation into a freeze dryer for secondary freeze drying. The freeze drying procedure is the same as S3.

[0064] The reconstitution time of the freeze-dried product in water is 12 minutes.

[0065] Embodiment 3:

[0066] S1: Preparation of freeze-dried solution: Take 44.44 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g of silk fibroin per 100 g of solution), 1.0 g of sodium hyaluronate, 1 g of trehalose, and 1.2 g of PEG-1000, and gently shake and mix.

[0067] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0068] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -30°C for 30 hours and a vacuum degree of 1 Pa.

[0069] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 2 minutes.

[0070] S5: Place the preparation after replacement pore formation into a freeze dryer for secondary freeze drying. The freeze drying procedure is the same as S3.

[0071] The reconstitution time of the freeze-dried product in water is 16 minutes.

[0072] Embodiment 4:

[0073] S1: Preparation of freeze-dried solution: 44.44 g of 4.5% wt. silk fibroin solution (molecular weight 160 kDa-200 kDa), 1.0 g of sodium hyaluronate, 1 g of trehalose, and 1.2 g of PEG-1000 were gently shaken and mixed.

[0074] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0075] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -20°C for 30 hours and a vacuum degree of 1 Pa.

[0076] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 2 minutes.

[0077] S5: Place the preparation after replacement pore formation into a freeze dryer for secondary freeze drying. The freeze drying procedure is the same as S3.

[0078] S6: In vitro cell assay

[0079] S61, cell scratch test: Human immortalized keratinocytes HaCaT were used, purchased from the Shanghai Cell Bank of the Chinese Academy of Sciences. The experimental temperature was 20-25°C, and the relative humidity was 60-70%. The in vitro cell wound healing experimental model was used to scratch the monolayer cells cultured in vitro, and then active repair substances were added to observe their ability to promote cell migration.

[0080] S62, in vitro inflammation characterization: RAW264.7 mouse macrophages were cultured in DMEM culture medium and 10% FBS fetal bovine serum. RAW264.7 cells with good morphology in the logarithmic growth phase were selected and inoculated in a 24-well plate and incubated in an incubator for 24 hours. A blank control group, an LPS-induced stimulation group, a positive control group (dexamethasone, dex) and a sample group were set up and incubated in a 37°C, 5% CO2 incubator for 2 hours. Except for the blank control group, LPS was added to each well and incubated in an incubator for 24 hours. The cell supernatant was tested according to the instructions of the ELISA kit and the nitric oxide detection kit, and the content of IL-6 and NO in the collected cell supernatant was detected, and the experimental results were analyzed by data processing software.

[0081] S63, in vitro cell sensitization characterization: THP-1 human acute monocytic leukemia cell line was cultured in DMEM culture medium and 10% FBS fetal bovine serum. The laboratory temperature was 20-25°C and the relative humidity was 60-70%. The cell survival rate and the expression of co-stimulatory molecules were determined by flow cytometry. The signal was obtained by collecting 10,000 cells by flow cytometry analysis. The expression of CD86 and CD54 molecules in each group was expressed by mean fluorescence intensity (MFI), and the degree of change in the expression of co-stimulatory molecules induced by the test substance was expressed by relative fluorescence intensity (RFI).

[0082]

[0083] 01). Carry out cell scratch test, the healing rate in 24 hours is 51%. The healing rate in 24 hours in the blank group is 7%, and the healing rate in 24 hours in the EGF 1000IU / mL group is 42%.

[0084] 02). Anti-inflammatory effect IL-6 expression score 0.7.

[0085] 03). Sensitization test-cell activity 92.6%

[0086] Embodiment 5:

[0087] S1: Preparation of freeze-dried solution: 44.44 g of 4.5% wt. silk fibroin solution (molecular weight 10 kDa-80 kDa), 1.0 g of sodium hyaluronate, 1 g of trehalose, and 1.2 g of PEG-1000 were gently shaken and mixed.

[0088] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0089] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -30°C for 25 hours and a vacuum degree of 1 Pa.

[0090] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 2 minutes.

[0091] S5: Place the preparation after replacement pore formation into a freeze dryer for secondary freeze drying. The freeze drying procedure is the same as S3.

[0092] S6: In vitro cell assay

[0093] S61, cell scratch test: Human immortalized keratinocytes HaCaT were used, purchased from the Shanghai Cell Bank of the Chinese Academy of Sciences. The experimental temperature was 20-25°C, and the relative humidity was 60-70%. The in vitro cell wound healing experimental model was used to scratch the monolayer cells cultured in vitro, and then active repair substances were added to observe their ability to promote cell migration.

[0094] S62, in vitro inflammation characterization: RAW264.7 mouse macrophages were cultured in DMEM culture medium and 10% FBS fetal bovine serum. RAW264.7 cells with good morphology in the logarithmic growth phase were selected and inoculated in a 24-well plate and incubated in an incubator for 24 hours. A blank control group, an LPS-induced stimulation group, a positive control group (dexamethasone, dex) and a sample group were set up and incubated in a 37°C, 5% CO2 incubator for 2 hours. Except for the blank control group, LPS was added to each well and incubated in an incubator for 24 hours. The cell supernatant was tested according to the instructions of the ELISA kit and the nitric oxide detection kit, and the content of IL-6 and NO in the collected cell supernatant was detected, and the experimental results were analyzed by data processing software.

[0095] S63, in vitro cell sensitization characterization: THP-1 human acute monocytic leukemia cell line was cultured in DMEM culture medium and 10% FBS fetal bovine serum. The laboratory temperature was 20-25°C and the relative humidity was 60-70%. The cell survival rate and the expression of co-stimulatory molecules were determined by flow cytometry. The signal was obtained by collecting 10,000 cells by flow cytometry analysis. The expression of CD86 and CD54 molecules in each group was expressed by mean fluorescence intensity (MFI), and the degree of change in the expression of co-stimulatory molecules induced by the test substance was expressed by relative fluorescence intensity (RFI).

[0096]

[0097] 01). Carry out cell scratch test, the healing rate is 27% in 24 hours. The healing rate of blank group is 7% in 24 hours, and the healing rate of EGF 1000IU / mL is 42% in 24 hours.

[0098] 02). Anti-inflammatory effect IL-6 expression score 0.0.

[0099] 03). Sensitization test-cell activity 92.0%

[0100] serial number Sample name Detection concentration IL-6 Sensitization test-cell activity% 01. Silk fibroin small molecules 0.0005% 0.0 92.0 02. Silk fibroin macromolecule 0.0005% 0.7 92.6

[0101] Comparative Example 1:

[0102] S1: Preparation of freeze-dried solution: Take 66.67 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g silk fibroin per 100 g solution), 0.5 g sodium hyaluronate, and 0.5 g PEG-1000, and gently shake and mix.

[0103] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0104] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -40°C for 30 hours and a vacuum degree of 1 Pa.

[0105] The freeze-dried preparation was visually completely dissolved in water in 67 minutes.

[0106] Comparative Example 2:

[0107] S1: Preparation of freeze-dried solution: 66.67 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g of silk fibroin per 100 g of solution) and 0.5 g of sodium hyaluronate.

[0108] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0109] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -40°C for 30 hours and a vacuum degree of 1 Pa.

[0110] The freeze-dried preparation was visually completely dissolved in water within 65 minutes.

[0111] Comparative Example 3:

[0112] S1: Preparation of freeze-dried liquid: 66.67 g of 4.5% silk fibroin solution (4.5% silk fibroin solution contains 4.5 g of silk fibroin per 100 g of solution) and 0.5 g of sodium hyaluronate.

[0113] S2: Forming: Packaging and forming, put 2g of the prepared lyophilized solution into a vial, and place it in a lyophilizer for forming;

[0114] S3: The pre-cooled preparation was placed in a freeze dryer for freeze drying at -40°C for 30 hours and a vacuum degree of 1 Pa.

[0115] S4: The freeze-dried preparation is immersed in ethanol to replace the pore-forming agent. The pore-forming time in ethanol is 2 minutes.

[0116] S5: Air-dry the preparation after replacement pore creation in a natural environment.

[0117] The ethanol in the freeze-dried preparation evaporates first, and then the preparation begins to absorb moisture and collapse, losing its original shape.

[0118] The porous silk fibroin preparation in Comparative Example 1 has an internal SEM as shown in FIG. Figure 2 As shown, there are obvious beads inside and the pores are uneven.

[0119] Summary: From the SEM images of Example 1 and Comparative Example 1, it can be seen that the pore-forming agent and the non-specific stabilizer significantly increase the internal pores of the freeze-dried product, thereby increasing the solubility of the product. From Examples 1, 2 and 3, it can be seen that the type of PEG has a slight effect on the re-dissolution time. The non-specific stabilizer has a certain protective effect on silk fibroin. From Comparative Examples 1 and 2, it can be seen that the re-dissolution time is at the hour level without replacing the pore-forming agent. From Comparative Example 3, it can be seen that the air-drying method without secondary freeze-drying destroys the product morphology.

[0120] It can be seen from Examples 4 and 5 that the high molecular weight silk fibroin composite high molecular weight sodium hyaluronate has better cell scratch repair and anti-inflammatory properties than the low molecular weight silk fibroin composite high molecular weight sodium hyaluronate. The cell sensitization test of the silk fibroin composite high molecular weight sodium hyaluronate showed excellent biocompatibility.

Claims

1. A method for preparing a porous silk fibroin freeze-dried preparation, characterized in that: The method comprises the following steps: S1 preparing a freeze-dried liquid, which comprises silk fibroin, sodium hyaluronate, a non-specific stabilizer and a pore-forming agent; S2 molding; S3 freeze-drying; S4 replacing the pore-forming agent; and S5 secondary freeze-drying.

2. The preparation method according to claim 1, comprising the following steps: S1: Preparation of lyophilized solution: sodium hyaluronate, non-specific stabilizer and pore-forming agent are added to the silk fibroin solution and mixed evenly. The concentration of silk fibroin includes but is not limited to 1 mg / mL-50 mg / mL; S2: Molding: The specific precooling method is one of S21 or S22; S21: Packaging and molding, packaging no more than 3.0 g of the freeze-dried component liquid into a mold and precooling; S22: Pre-cooling molding, three-dimensional structure with the distance between the farthest two points not exceeding 5mm (including: cube, cuboid, cylinder, sphere, etc.); S3: placing the pre-cooled preparation in a freeze dryer for primary freeze drying; S4: immersing the once lyophilized preparation in ethanol for pore former replacement; S5: Place the preparation after replacement pore creation into a freeze dryer for secondary freeze drying.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, by mass ratio, silk fibroin: sodium hyaluronate: non-specific stabilizer: pore-forming agent = 1.0-7.0: 0.5-4.0: 0.5-4.0: 0.5-4.0, the non-specific stabilizer system includes one or more of I, II, and III, and the pore-forming agent is shown in IV. Specific examples are as follows: Nonspecific Stabilizers: I: Sugar substances such as trehalose, lactose, sucrose, maltose, caramel II: Sugar alcohols such as mannitol, sorbitol, xylitol, erythritol III: Cellulose derivatives such as sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose Pore ​​forming agent: IV: Polyethylene glycol such as PEG-400, PEG-600, PEG-800, PEG-1000.

4. The preparation method according to any one of claims 1 to 3, wherein S4 comprises immersing the once freeze-dried product in ethanol to form pores, and the immersion in ethanol to form pores time is 5 seconds to 20 minutes.

5. The preparation method according to any one of claims 1 to 4, S5 comprises placing the pore-forming product into a freeze dryer for secondary freeze drying.

6. A porous silk fibroin freeze-dried preparation prepared by the preparation method according to any one of claims 1 to 5.

7. The porous silk fibroin freeze-dried preparation according to claim 6, characterized in that: The pore size inside the freeze-dried preparation is ≥10 μm, the porosity is ≥85%, and the pore size deviation is <5 μm.

8. Use of the porous lyophilized silk fibroin preparation according to the preparation method of any one of claims 1 to 5 or the porous lyophilized silk fibroin preparation according to any one of claims 6 to 7, characterized in that: The applications include: dressing products, hydrating products and filling products.

Citation Information

Cited By

  • Silk fibroin solution injection capable of forming gel in situ as well as preparation method and application of silk fibroin solution injection

    CN120733118A